Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Non Fisik terhadap Kinerja Karyawan pada bagian produksi automotive di PT Seikou Seat Cover - Zulfahmi, Rio; Sarah, Siti (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to analyze the influence of Leadership Style, and Non-Physical Work Environment on Employee Performance in the automotive production section at PT Seikou Seat Cover using quantitative research methods and verification and descriptive analysis approaches. Primary data used can be by distributing pre-surveys, questionnaires, document collection, and interviews with employees of PT Seikou Seat Cover. The research sample taken using the method The sampling technique used in this study is Probability Sampling with a stratified random sampling method (Stratified Random Sampling), a method based on strata or levels, namely the level is only non-managerial. The sample in this study was drawn from private employees, while the managerial level and above were not sampled, so that 67 employees were obtained as the population and research sample. The results of the regression analysis show that Leadership Style and Non-Physical Work Environment significantly affect Employee Performance. The results of the determination coefficient show a value of 0.915 or 91.5%, which means that there is a strong relationship between Leadership Style and Non-Physical Work Environment on Employee Performance with a contribution of 0.837 or 83.7%. While the remaining 16.3% is applied to other variables.